Abnormal NMDA receptor function exacerbates experimental autoimmune encephalomyelitis. (20th December 2012) - Grasselli, G; Rossi, S; Musella, A; Gentile, A; Loizzo, S; Muzio, L; Di Sanza, C; Errico, F; Musumeci, G; Haji, N; Fresegna, D; Sepman, H; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Glutamate transmission is dysregulated in both multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), the animal model of MS. A characteristic of EAE is increased glutamate transmission associated with up‐regulation of AMPA receptors. However, little is known about the role of NMDA receptors in the synaptic modifications induced by EAE. Experimental Approach The contribution of NMDA receptors to the alterations of glutamate transmission and disease severity in EAE mice was assessed by means of neurophysiological, morphological, Western blot, metabolic and clinical score assessments. Key Results In our EAE mice, there was an NMDA receptor‐dependent increase of glutamate release, associated with marked activation of the astroglia. Presynaptic NMDA receptors became overactive during EAE, increasing synaptic glutamate release by a mechanism dependent on voltage‐gated sodium channels. By means of NAD(P)H autofluorescence analysis, we also found that EAE has a glutamate and NMDA receptor‐dependent dysfunction of mitochondrial activity, which is known to contribute to the neurodegenerative damage of MS and EAE. Furthermore, pharmacological blockade of NMDA receptors in vivo ameliorated both synaptic transmission defects and of the clinical disease course of EAE mice, while EAE induced in mice with a genetically enhanced NMDA receptor signalling had opposite effects. Conclusions and Implications Our data, showing both sensitization of NMDA receptors and their involvement in the progression of the EAE disease, supggest that pharmacological impairment of NMDA receptor signalling would be a component of a neuroprotection strategy in MS.